Shikonin Inhibits Fin Regeneration in Zebrafish Larvae - Zigang Cao; Chen Guo; Guilan Chen; Jiejun Liu; Huiwen Ni; Fangsheng Liu; Guanghua Xiong; Xinjun Liao; Huiqiang Lu (Cells, 2022)
Shikonin is a naphthoquinone compound extracted from Chinese comfrey for treating cancer. However, there are few reports on its research on vertebrate tissue regeneration. Zebrafish is an ideal model for studying organ regeneration. In this study, we found that 3-dpf of zebrafish larvae exposed to shikonin at concentrations of 0.2, 0.3, and 0.4 mg/L showed increasingly inhibited regeneration of the tail fin. Immunohistochemical staining showed that shikonin exposure from 6 to 12 hpa increased the number of apoptotic cells in the caudal fin wound of larvae and decreased the number of proliferating cells. Shikonin exposure was found to up-regulate oxidative stress, increase ROS levels, and reduce neutrophil recruitment in the early stage of wound repair. Moreover, shikonin exposure caused disordered expression of fin regeneration blastemal-related genes. The use of astaxanthin to down-regulate oxidative stress was found to significantly reduce the inhibition of caudal fin regeneration. Mixed exposure of AMPK inhibitors or fullerenes (C60) with shikonin also showed the similar rescue effect. Collectively, our study showed that shikonin inhibited fin regeneration in zebrafish larvae by the upregulation of oxidative stress level and AMPK signaling pathway. This research provides valuable information on the mechanism of action of shikonin for its safe application.